A geology for engineers - Blyth, F. G. H.; De Freitas, M. H. (CRC Press, Taylor & Francis Group, 2017)
No engineering structure can be built on the ground or within it without the influence of geology being experienced by the engineer. Yet geology is an ancillary subject to students of engineering and it is therefore essential that their training is supported by a concise, reliable and usable text on geology and its relationship to engineering. In this book all the fundamental aspects of geology are described and explained, but within the limits thought suitable for engineers. Specific instruction is provided on the relationship between geology and many common activities undertaken when engineering in rock and soil.